Face Masks Considerably Reduce COVID-19 Cases in Germany: A Synthetic Control Method Approach - Timo Mitze; Reinhold Kosfeld; Johannes Rode; Klaus Wälde (Institute of Labor Economics (IZA), 2020)
We use the synthetic control method to analyze the effect of face masks on the spread of Covid-19 in Germany. Our identification approach exploits regional variation in the point in time when face masks became compulsory. Depending on the region we analyse, we find that face masks reduced the cumulative number of registered Covid-19 cases between 2.3% and 13% over a period of 10 days after they became compulsory. Assessing the credibility of the various estimates, we conclude that face masks reduce the daily growth rate of reported infections by around 40%.
Keywords: I18; C23; 330; COVID-19; public health measures; face masks; synthetic control method; Germany